Eficácia dos antagonistas beta-adrenérgicos no tratamento de disfunções temporomandibulares dolorosas: uma revisão sistemática de ensaios clínicos randomizados com metanálise - Albuquerque, Mayara Fontenele (2023)
Background: The autonomic nervous system in pain states plays a facilitatory role in the generation and processing of nociceptive signals. In this way, beta-adrenergic antagonist (βAA) has been advocated for treatment of painful temporomandibular disorders (TMDs), but its effectiveness for painful TMD is unclear. The purpose of this systematic review is to investigate the analgesic effectiveness of βAA in painful TMD patients. Methods: This study was registered on PROSPERO (n. CRD42020183370). An electronic search was performed in PubMed, Web of Science, Scopus, Science Direct, Embase, LILACS BIREME Virtual Health Library (Latin American and Caribbean Health Science Information database), Livivo, Cochrane Central Register of Controlled Trials, US National Institutes of Health Ongoing Trials Register (clinicaltrials.gov), Google Scholar, OpenGrey, PubMed Central, BDTD (Brazilian Digital Library of Theses and Dissertations), OpenThesis, and ProQuest. The search included randomized controlled trials (RCTs) on TMD patients that investigated the effects of βAA reduction of pain, pressure pain threshold (PPT) and jaw opening. The risk of bias and the quality of evidence were assessed respectively by the updated Cochrane Risk of Bias (RoB) tool: RoB 2 and the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: Five RCTs were eligible for qualitative synthesis and three RCTs were included for meta-analysis including a total of de 315 patients, with overall RoB settings ranging from low, some concerns, or high. The meta-analysis for the pain intensity outcome did not demonstrate clinical benefit of βAA treatment (Cohen's d = -0.21, 95%CI = -0.44 to 0.01), although propranolol seems to have some effectiveness in reducing TMD pain among migraine patients. No clinical benefit from the use of βAA was observed in patients with TMD for pressure pain threshold (p=0.090) and jaw opening (p=0.680). Conclusion: βAA administration has little evidence of effectiveness for the treatment of painful TMD.